2020
DOI: 10.3390/jcm9041021
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Hormonal Biomarkers in Cachectic Elderly Women with Chronic Heart Failure

Abstract: Background: Cachexia is an unfavorable metabolic syndrome causing involuntary weight loss followed by muscle wasting, which can lead to the exacerbation of chronic heart failure (CHF), and considerably increases mortality rate among CHF patients. Unfortunately, until now it has not been possible to determine factors that could improve clinical options for cachexia management or enable the identification of patients at risk of its development. We assessed how cachexia conditions in CHF reflect cardiac and labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Irisin levels demonstrated positive correlation with brain natriuretic peptide (BNP) levels and New York Heart Association (NYHA) class of HF and inverse correlation with body mass index (BMI) and catabolic state including cachexia in HFrEF [ 69 ]. Yet, FNDC5 expression in skeletal muscles is related to aerobic performance in patients with HFrHF [ 70 , 71 ]. Thus, irisin plays a protective role in myocardial ischemia, cardiac myocyte apoptosis, and skeletal myopathy preserving energy homeostasis, attenuating mitochondrial function, and regulating muscle atrophy.…”
Section: Myokines In Hf Myopathymentioning
confidence: 99%
“…Irisin levels demonstrated positive correlation with brain natriuretic peptide (BNP) levels and New York Heart Association (NYHA) class of HF and inverse correlation with body mass index (BMI) and catabolic state including cachexia in HFrEF [ 69 ]. Yet, FNDC5 expression in skeletal muscles is related to aerobic performance in patients with HFrHF [ 70 , 71 ]. Thus, irisin plays a protective role in myocardial ischemia, cardiac myocyte apoptosis, and skeletal myopathy preserving energy homeostasis, attenuating mitochondrial function, and regulating muscle atrophy.…”
Section: Myokines In Hf Myopathymentioning
confidence: 99%
“…Cachexia is caused by muscle wasting and the exacerbation of heart failure decompensation. A low level of circulating irisin was noted in female patients with heart failure with cachexia [69]. By contrast, another study showed a high level of irisin in heart failure with cachexia [70].…”
Section: Irisin In Patients With Heart Failurementioning
confidence: 82%
“…Higher irisin might enhance the energy demand and produce more oxidative stress. In the chronic heart failure stage, lower irisin might represent muscle loss and cachexia [69]. However, we need a large cohort study to prove this observation in the future.…”
Section: Irisin In Patients With Heart Failurementioning
confidence: 93%
“…Chronic heart failure (CHF) is a clinical syndrome characterized by systemic inflammation and immune system activation [ 1 ]. The increase in the number of newly diagnosed CHF cases is related to a rising life expectancy (patient’s age >70 years) and diastolic heart failure [ 2 , 3 ]. Inflammation plays a crucial role in chronic heart failure.…”
Section: Introductionmentioning
confidence: 99%